The variability of automated QRS duration measurement - Vancura, Vlastimil; Wichterle, Dan; Ulc, Ivan; Šmíd, Jirí; Brabec, Marek; Zárybnická, Marta; Rokyta, Richard (Europace, 2017)
AIMS: Previous studies have demonstrated substantial variability in manual assessment of QRS complex duration (QRSd). Disagreements in QRSd measurements were also found in several automated algorithms tested on digitized electrocardiogram (ECG) recordings. The aim of our study was to investigate the variability of automated QRSd measurements performed by two commercially available electrocardiographs. METHODS AND RESULTS: Two GE MAC 5000 (GE-1 and GE-2) electrocardiographs and two Mortara ELI 350 (Mortara-1 and Mortara-2) electrocardiographs were used in the study. Participants for the study were recruited from patients hospitalized in the department of cardiology of a university hospital. Participants underwent up to four recording sessions within a single day with a different electrocardiograph at each session when two to four immediately successive ECG recordings were undertaken. In 76 patients, 683 ECGs were recorded; the mean QRSd was 109.0 ± 26.1 ms. The QRSd difference ≥10 ms between the first and second intra-session ECG was found in 7, 3, 20, and 14% of ECG pairs for GE-1, GE-2, Mortara-1, and Mortara-2, respectively. No inter-session difference in QRSd was found within both manufacturers. In individual patients, Mortara calculated the mean QRSd to be longer by 7.3 ms (95% CI: 6.2-8.5 ms, P < 0.0001) with a 2.1-times (95% CI: 1.9-2.4) greater standard deviation of the mean QRSd (7.1 vs. 3.3 ms, P < 0.001). CONCLUSION: Electrocardiographs from two manufacturers measured QRSd values with a systematic difference and a significantly different level of precision. This may have important clinical implications in selection of suitable candidates for cardiac resynchronization therapy.
Keywords: QRS complex; Equipment Design; analýza selhání vybavení; diagnóza počítačová; Reproducibility of Results; lidé; Sensitivity and Specificity; ECG; senzitivita a specificita; Automated measurement; Equipment Failure Analysis; Electrocardiography; Algorithms; elektrokardiografie; Pattern Recognition, Automated; rozpoznávání automatizované; reprodukovatelnost výsledků; Aged; algoritmy; senioři; design vybavení; Diagnosis, Computer-Assisted; Humans